2013
DOI: 10.1590/s1516-35982013001200001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment and packaging systems on the stability of fish sausage

Abstract: -The purpose of this study was to evaluate the physicochemical and microbiological stability of sausages produced from mechanically separated fish meat (MSM) obtained from Nile tilapia filleting residues. Different heat treatments (pasteurization or smoking) and packaging systems (conventional or vacuum) were used. The sausages were characterized for chemical composition, weight loss, water activity, instrumental texture and sensorial analysis. Additionally, microbiological analysis, instrumental color, pH, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
0
16
0
4
Order By: Relevance
“…The pH results meet Brazil's legislation for fresh fish (Brasil, 2001a). Higher values of pH were obtained by Oliveira Filho et al (2010) and Dallabona et al (2013) in sausages prepared with the addition of MSM at time 0 storage. The mean Aw value did not reveal any significant differences (p > 0.05) between the formulations and treatments.…”
Section: Physical and Chemical Compositionmentioning
confidence: 78%
See 1 more Smart Citation
“…The pH results meet Brazil's legislation for fresh fish (Brasil, 2001a). Higher values of pH were obtained by Oliveira Filho et al (2010) and Dallabona et al (2013) in sausages prepared with the addition of MSM at time 0 storage. The mean Aw value did not reveal any significant differences (p > 0.05) between the formulations and treatments.…”
Section: Physical and Chemical Compositionmentioning
confidence: 78%
“…Fishburgers with tilapia MSM had means between 7.14 and 7.46 for all attributes, and the mean scores for buying intention varied between 3.86 and 3.98 (Marengoni et al, 2009). Overall acceptance of sausages with 64% MSM of tilapia, smoked and pasteurized, ranged between 7.7 and 7.5, respectively (Dallabona et al, 2013).…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…Meanwhile, the coliforms were not detected in both dried fish samples. Similarly, no presence of Escherichia coli was detected in stored fish sausages that were treated with thermal process [ 33 ]. The TPC in dried common carp surimi was 1.70 × 10 1 cfu/g and coliform were not detected and this may be due to the effect of processing of surimi that destroying microorganisms in tissues [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Minozzo [15] and Dallabona et al, [16] found data close to Table 2 for the texture attribute when evaluating the sensory quality of MSM mortadella of Tilapia, obtaining averages scores of 7.20 and 7.50, respectively, corresponding to the term "I liked it moderately". Evaluating the emulsified sausage texture of MSM Nile Tilapia, Lago et al [14] obtained an average score lower than the one from this study (6.02), as well as Bernadino Filho et al, [17] who obtained an average score of 6.80 when evaluating the mortadella texture prepared with flying fish surimi.…”
Section: According Tomentioning
confidence: 73%